PERANCANGAN DAN PERHITUNGAN ELEMEN MESIN PENCETAK PELET MAGGOT SISTEM EXTRUDER - nuraini lusi (Politeknik Negeri Madura, 2020)
Bioconversion has indeed begun to be developed a lot recently. Through this process, the nutrient content in organic waste can be formed into other forms of nutrients, namely biomass with the help of insect larvae, one of which is the insect larvae of Hermetia illucens / Black Soldier Fly (BSF). Larvae of this type are often used as bioconversion agents and are better known as